Small Enterprise Investment Scheme Analysis: A study on Al Arafah Islami Bank Limited - Nabil, Abdullah Naser (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.